Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/hlca.200690059
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids from Eupatorium fortuneiTurcz

Abstract: Four new terpenoids, namely, rel-(1R,2S,3R,4R,6S)-p-menthane-1,2,3,6-tetrol (1), rel-(1R,2R,3R,4S,6S)-p-menthane-1,2,3,6-tetrol (2), 9-hydroxythymol 3-O-angelate (3), and (3b,20R)-20hydroxylanost-25-en-3-yl palmitate (4), together with fourteen known compounds, were isolated from the AcOEt part of the MeOH extracts of Eupatorium fortunei. In addition, two other monoterpenoids, 'acetone thymol-8,9-diyl ketal' (19) and 8-methoxy-9-hydroxythymol 3-O-angelate (20) were also obtained which were probably artifacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…The relative configuration at C(1) was determined from ROESY correlation of δ 1.21 (Me(7)) with H-2 ( δ 3.33). It was in good agreement with those of rel- (1 R ,2 S ,3 R ,4 R ,6 S ) p -menthane-1,2,3,6-tetrol [8]. Therefore 1 should possess rel -(1 R ,2 S ,3 R ,4 R )-configuration.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The relative configuration at C(1) was determined from ROESY correlation of δ 1.21 (Me(7)) with H-2 ( δ 3.33). It was in good agreement with those of rel- (1 R ,2 S ,3 R ,4 R ,6 S ) p -menthane-1,2,3,6-tetrol [8]. Therefore 1 should possess rel -(1 R ,2 S ,3 R ,4 R )-configuration.…”
Section: Resultssupporting
confidence: 73%
“…The 1 H- and 13 C-NMR spectral data displayed the presence of two secondary methyl δ 0.81 (3H, d J  = 7.0 Hz, H-10), 0.92 (3H, d J  = 7.0 Hz, H-9)], a tertiary methyl δ 1.21 (3H, s , H-7)], two methylenes δ 1.37 (2H, dt J  = 11.7, 8.3 Hz, H-5), 1.40 (1H, m, H-6α) and 1.57 (1H, m, H-6β)], four methines (two of them was oxygenated) δ 3.82 (1H, d J  = 10.8, 9.2 Hz, H-3), 3.33 (1H, d J  = 10.8 Hz, H-2), 2.31 (1H, m, H-8), and 1.69 (1H, m, H-4)], and an oxygentated quaternary carbon, suggesting that compound 1 was a menthane-type monoterpene with three OH-groups [7,8]. Moreover, 1 H- 1 H COSY correlations were observed between H-C(9)/H-C(8)/H-C(10), H-C(8)/H-C(4), and H-C(6)/H-C(5)/H-C(4)/H-C(3)/H-C(2), that the deduced spin system implied that the three OH-groups were located at C(1), C(2) and C(3) in 1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 2-6 were identified as grasshopper ketone (3S,5R,8R)-3,5-dihydroxy megastigma-6,7-dien-9-one (Jiang et al, 2006), citroside A [(3S,5R,8R)-3,5-dihydroxymega stigma-6,7-dien-9-one-3-O-β-D-glucopyranoside (Wang et al, 2005), vomifoliol [(6S,9R) 6-hydroxyl-3-oxo-α-ionol] (Otsuka et al, 1995), (6S,9R)-3-oxo-α-ionol-9-O-β-Dglucopyranoside (Dwivedi et al, 1991), and (6S,9R)-3-oxo-α-ionol-9-O-β-D-glucopyranoside (Otsuka et al, 1995) with the help of spectroscopic techniques, respectively. Their 1 H-NMR and 13 C-NMR data were in agreement with the ones reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, p- cymene and neryl acetate, major components of E. fortunei , have been reported to possess anti-influenza activity. In a recent study, it was demonstrated that the ethyl acetate fraction of a methanol extract of E. fortunei exhibited cytotoxicity against human leukemia (HL-60) cells 20 .…”
mentioning
confidence: 99%